Role of tumor microenvironment in the pathobiology of ovarian cancer: Insights and therapeutic opportunities. (21st August 2018) - Ghoneum, Alia; Afify, Hesham; Salih, Ziyan; Kelly, Michael; Said, Neveen
Abstract: Ovarian cancer is the fifth most common cancer affecting women and at present, stands as the most lethal gynecologic malignancy. The poor disease outcome is due to the nonspecific symptoms and the lack of effective treatment at advanced stages. Thus, it is of utmost importance to understand ovarian carcinoma through several lenses and to dissect the role that the unique peritoneal tumor microenvironment plays in ovarian cancer progression and metastasis. This review seeks to highlight several determinants of this unique tumor microenvironment, their influence on disease outcome and ongoing clinical trials targeting these determinants. Abstract : Ovarian cancer is the fifth most common cancer affecting women and at present, stands as the most lethal gynecologic malignancy. A major cause of poor disease outcome is attributed to nonspecific symptoms and below par diagnostic criteria at early phases along with a lack of effective treatment at advanced stages. Thus, it is of utmost importance to understand ovarian carcinoma through several lenses and to dissect the role that the unique peritoneal tumor microenvironment plays in ovarian cancer progression and metastasis. This review seeks to highlight several determinants of this unique tumor microenvironment, their influence on disease outcome and ongoing clinical trials targeting these determinants.